Begagan Sub-Village’s Community Readiness To Develop A Tourism Village - Manuela Octaviani; Ribut Basuki (Institute of Research and Community Outreach - Petra Christian University, 2023)
This paper figures out whether the communities in Begagan sub-village as a part of Begaganlimo village in Mojokerto, East Java, are ready to develop a tourism village. This study uses descriptive qualitative approach. Data are collected through questionnaires and interviews. The data are then analyzed using readiness criteria to find out the communities’ readiness and the reasons why they are ready or otherwise. The results show that the communities are ready to develop a tourism village. They have high motivation, related to having better income and preserving their local culture. The communities are also ready for any change socially due to the development of the tourism village. They have healthy relationships with others and have high awareness towards keeping the environment intact. They are aware that their areas have attractions in the form of scenery, culture, and products and are quite eager to develop their sub-village, and thus village, to become tourism village. However, they have problems in funding and better training to develop a marketable tourism village.